7.74x+9=59.9076+3x

Simple and best practice solution for 7.74x+9=59.9076+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7.74x+9=59.9076+3x equation:



7.74x+9=59.9076+3x
We move all terms to the left:
7.74x+9-(59.9076+3x)=0
We add all the numbers together, and all the variables
7.74x-(3x+59.9076)+9=0
We get rid of parentheses
7.74x-3x-59.9076+9=0
We add all the numbers together, and all the variables
4.74x-50.9076=0
We move all terms containing x to the left, all other terms to the right
4.74x=50.9076
x=50.9076/4.74
x=10+2.3266118333776/3.1440700451048

See similar equations:

| 7(x+1)=98 | | 10x-5=48 | | 1-3x=4x+1 | | q/7-4=2 | | 2(-7x+50+2x=3x+3-15x | | Y+21=8y-63 | | −1/4x=10 | | 5/3-(-6e)=4/3 | | -16x^2+160x+128=0 | | 16y+1–13y=–17 | | 5(p-75)=95 | | 2x+12=-3x-13 | | 4w-41=6w-75 | | 0.4(10x+11)=3(0.2x+5) | | -7-6x=-25 | | 7x^2-4x=x(7x-4) | | 15x+3=10x=3 | | 47/r=12 | | 6/7s=18 | | z-66/3=9 | | 2.3-1.5x=5.3 | | 10(k+5)+11=8k-5 | | 4(y-65)=56 | | v-5.85=1.6 | | -2(x+7)+10=(2x+x+2)-1 | | 4/11x-1/12=6x | | 5m+2=3m+15 | | 2y-64=y+70 | | 5a/9=25 | | 16y-14y+2y-2y=14 | | 450=9x+405 | | u+42/9=9 |

Equations solver categories